Detection of Avian Orthoavulavirus-1 genotypes VI.2.1 and VII.1.1 with neuro-viscerotropic tropism in some backyard pigeons (Columbidae) in Eastern Saudi Arabia - Al-Mubarak, Abdullah I. A.; Al-Kubati, Anwar A. G.; Sheikh, Abdullah; Abdelaziz, Adel M.; Hussen, Jamal; Kandeel, Mahmoud; Falemban, Baraa; Hemida, Maged Gomaa (Frontiers in Veterinary Science, 2024)
Avian orthoavulavirus-1 (AOAV1) has a wide host range, including domestic and wild birds. The present study aimed to identify the currently circulating AOAV1 strains from some outbreaks in some backyard pigeons in the eastern region of Saudi Arabia (ERSA). Tracheal/cloacal swabs and tissue specimens were collected from eight backyards in Al-Ahsa, ERSA, between January 2021 and March 2023. Samples were tested for the presence of AOAV1 using commercial real-time RT-PCR. Part of the fusion gene was also amplified by gel-based RT-PCR, and the obtained amplicons were sequenced. AOAV1 was detected in samples from the eight flocks. The retrieved sequences from samples of 6/8 pigeon backyards are reported. Phylogenetic analysis based on the obtained sequences from these backyard pigeons showed the segregation of the obtained sequences in AOAV1 genotypes VI.2.1 and VII.1.1. Clinically, nervous manifestations were dominant in pigeons infected with both genotypes. Respiratory manifestations and significantly higher overall mortality rate were induced by genotype VI.2.1. The deduced amino acid sequences of the fusion protein cleavage site (FPCS) showed that all the detected isolates belong to velogenic strains. Differences in clinical profiles induced by the natural infection of pigeons with AOAV1 genotypes VI.2.1 and VII.1.1 were reported. The present findings highlight the potential roles of some backyard pigeons in the long-distance spread and cross-species transmission of the reported AOAVI genotypes. Further research is required to perform biotyping and pathotyping of the reported strains.